Early stages of notothenioid fish from Potter Cove, South Shetland Islands - Piacentino, Gabriela Laura Maria; Moreira, María Eugenia; Barrera Oro, Esteban (Polar Biology)
At Potter Cove, King George Island/Isla 25 de Mayo, South Shetland Islands, significant ichthyological research has been conducted in the last three decades, mainly on the general ecology of notothenioid species in demersal stages from young juveniles to adults. Nevertheless, the knowledge of the ichthyoplankton composition in the cove, necessary for the overall comprehension of the dynamics of the fish species life-cycles, remained unexplored. Here, we report the first record of the early stages of Antarctic notothenioids collected in pelagic hauls at Potter Cove in summer 2014 and 2016 at depths of 6–9 m where total bottom depth ranged 30–190 m. The ichthyoplankton was represented by members of the families Harpagiferidae, Nototheniidae and Bathydraconidae. It consists of (1) 37 larval stages (preflexion and postflexion) of the species Harpagifer antarcticus (the most abundant), Psilodraco breviceps, Lepidonotothen squamifrons, Pleuragramma antarcticum and Trematomus scotti, and (2) 15 eggs of Notothenia coriiceps, of which two larvae hatched in the aquarium. Part of this material is illustrated by photographs. The presence of early life stages of fish in the cove is linked to the major influx from the Bransfield Strait and also depends on local environmental conditions (i.e., hydrologic, water circulation). In addition to being a spawning site for Parachaenichthys charcoti, already reported in the literature, nearshore localities of the South Shetland Islands such as Potter Cove appear to also be spawning sites for N. coriiceps, H. antarcticus and Chaenocephalus aceratus. Fil: Piacentino, Gabriela Laura Maria. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales “Bernardino Rivadavia”; Argentina Fil: Moreira, María Eugenia. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto ...